Power and society in conditions of military-political and economic crisis: the Kuban-Black Sea region in the early 1920s. - Yuri Aslanbievich Yakhutl (Кавказология, 2023)
The Bolsheviks’ relationship with the rural population of the Kuban-Black Sea region was marked by the active use of war communist methods from the moment Soviet power was restored and before the actual implementation of the main provisions of food and land policy in the structure of the NEP. Repression against the rural population, as well as forced food confiscation, ultimately led to a rise in military-political confrontation between the government and society. The interval between an official military-communist policy and the practical implementation of the NEP in the region lasted up to a year and a half, ending in 1923. The challenges of the transition phase, as well as the construction of a model of the connection between the RCP (b) and the region’s populace, were largely explained by the region’s peculiarities, which blended class, class, and interethnic tensions. As a result, the Bolsheviks agreed to a compromise in the following round of reforms, which began in 1924 as part of the “Facing the Countryside” course, abandoning coercive tactics in domestic affairs.